Molecular cloning and characterization of the gene encoding the adenine methyltransferase M.CviRI from Chlorella virus XZ-6E. - Stefan, C (1991)
The gene encoding the DNA methyltransferase M.CviRI from Chlorella virus XZ-6E was cloned and expressed in Escherichia coli. M.CviRI methylates adenine in TGCA sequences. DNA containing the M.CviRI gene was sequenced and a single open reading frame of 1137 bp was identified which could code for a polypeptide of 379 amino acids with a predicted molecular weight of 42,814. Comparison of the M.CviRI predicted amino acid sequence with another Chlorella virus and 14 bacterial adenine methyltransferases revealed extensive similarity to the other Chlorella virus enzyme.